The Effect of Guided Imagery in Reducing Pain Intensity in Costa Fracture Patients with Levine Theory Approach: A Case Study - Tri Wahyuni, Anna; purwanto, purwanto (An Idea Nursing Journal, 2024)
: Background: Pain in fracture patients is one of the symptoms of a partial or total bone tissue discontinuity damage that causes discomfort. One of the nonpharmacological therapies used according to evidence-based nursing is guided imagery. People with health problems ranging from musculoskeletal problems to terminal illnesses have used guided imagery to relieve symptoms, find meaning, stimulate healing, and make changes, stimulate healing, and make important lifestyle changes that support and encourage healing. However, the use of this implementation is still minimal in nursing. Therefore, this research study was conducted to assess the effect of guided imagery in reducing pain intensity, especially in fracture patients. Method: The method of writing this article uses case studies in patients with costa fractures. Results and Discussion: After 3 days of guided imagery with Levine's theoretical approach, pain decreased from a scale of 6/10 to 3/10. Conclusions: Guided imagery is effective in reducing pain with Levine's theory approach in costa fracture patients.